Answer:
The new function is g(x) = x² +1
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given that the function f(x) = x²
From graph ,
The parabola y = x² is shifting to up with '1' units
y = x² +1
The new function is g(x) = x² +1
<u><em>Verification:-</em></u>
y = x²+1
Put x=0 ⇒ y =1
The point (0,1) lies on the parabola y = x²+1
similarly put x =1 and y = 2
The Point (1,2) lies on the Parabola y = x²+1
∴ The new graph y = x²+1
<span> we have that
standard form of equation for parabola:
(x-h)^2=-4p(y-k)
(h,k) --------->being the (x,y) coordinates of the vertex.
Parabola opens downwards because focus is below vertex on the axis of symmetry.
For given problem:
</span><span>vertex: (-3,2)
axis of symmetry: x=-3
p=distance from vertex to focus on the axis of symmetry=2-(-1)=3
4p=12
Directrix: y=2+p=5
Equation:
(x+3)^2=-12(y-2)
the answer is </span>(x+3)^2=-12(y-2)
Answer:
straight ?
Step-by-step explanation:
Answer:
k = 140°
Step-by-step explanation:
The sum of the interior angles of any triangle = 180°.
64° + 76° + x = 180°
x = 40°
40° + k = 180° because they are supplementary angles
k = 140°